Eye acupuncture therapy for insomnia: a systematic review and network meta-analysis - Shi, Zhenyu; Wang, Shuxuan; Sun, Di; Liu, Hao; Wang, Yaqun; Xu, Cheng (Frontiers in Neurology, 2025)
ObjectiveThis study aims to comprehensively evaluate the efficacy and safety of eye acupuncture as a treatment modality for insomnia using advanced network Meta-analysis techniques.MethodsA systematic and thorough search was performed across eight major databases, spanning from their inception to September 01, 2025, to identify pertinent studies. In accordance with a rigorous screening process, which involved assessing titles, abstracts, and full-text articles, we performed data extraction and quality appraisal.ResultsA total of 31 studies, which encompassed a diverse range of interventions, were included for detailed analysis and synthesis. The findings revealed that both eye acupuncture (EA) alone and in conjunction with other treatments, such as pharmacotherapy and non-pharmacotherapy interventions, exhibited superior efficacy compared to non-utilization of EA in ameliorating patient conditions, as evaluated through Clinical Effectiveness, Pittsburgh Sleep Quality Index score (PSQI), and Chinese Medicine Symptom Complex Score (CMSCS). The Network Meta-analysis findings revealed notable disparities in Clinical Effectiveness, PSQI, and CMSCS between interventions incorporating EA or its combination with other modalities and those not utilizing EA. Particularly, the combination of EA with body acupuncture (BA) ranked highest in reducing PSQI and CMSCS, while the combination with wrist-ankle acupuncture (WA) showed superior Clinical Effectiveness. Although the funnel plots displayed a mostly symmetrical distribution, indicating potential small sample effects and publication bias, it's crucial to interpret these results alongside clinical syndrome differentiation and treatment strategies.ConclusionsCompared to non-utilization of EA, its application demonstrates superior therapeutic efficacy in ameliorating insomnia symptoms among affected individuals. However, further validation through large-scale, multi-center, and high-quality studies is imperative to strengthen this conclusion.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42023491548, identifer: CRD42023491548.